Athanas alpheusophilus sp. nov. (Decapoda: Alpheidae)—a new Alpheus-associated shrimp from the Russian coast of the Sea of Japan - Marin, Ivan (Zootaxa, 2017)
A new alpheid shrimp, Athanas alpheusophilus sp. nov., is described on the basis of numerous mature specimens collected from burrows of Alpheus brevicristatus De Haan, 1844 in Vityaz Bay, which is part of Posjeta Bay on the Russian side of the Sea of Japan. The new species belongs to “Athanas dimorphus” species complex and can be clearly separated from Athanas japonicus Kubo, 1936 and relative species by unique combination of morphological features of male and female pereiopods I (chelipeds) and some other features. Moreover, Athanas alpheusophilus sp. nov. is the first species of the genus Athanas Leach, 1814 reported as a symbiont of larger burrowing snapping shrimps of the genus Alpheus Fabricius, 1798 (Crustacea: Decapoda: Alpheidae). Some taxonomic remarks on A. japonicus and related species are provided and Athanas lamellifer Kubo, 1940 is revalidated based on morphology of the male pereiopods I.